Are Co‐users of Alcohol and Marijuana More Willing to Experience Consequences From Drinking? A Longitudinal Examination Among First‐Year College Students. (28th May 2019) - Linden‐Carmichael, Ashley N.; Mallett, Kimberly A.; Sell, Nichole; Turrisi, Robert
Abstract : Background: Alcohol and marijuana co‐users are at heightened vulnerability for experiencing a variety of negative alcohol use outcomes including heavier alcohol use and driving under the influence. The current study explored willingness to experience negative consequences as a potential factor underlying the association between co‐user status and negative consequences in an effort to guide future intervention work. From a longitudinal study of first‐year college students, we examined willingness to experience consequences at Time 2 as a mediator of co‐user status at Time 1 and experience of negative consequences at Time 3. Methods: First‐year college student drinkers ( n  = 1, 914) at a large university completed surveys in the fall and spring of their freshman year and the fall of their sophomore year. Results: Alcohol and marijuana co‐users reported higher willingness to experience consequences than alcohol‐only users. Willingness to experience consequences partially explained the association between alcohol and marijuana couse and consequences. Conclusions: The current study was the first to compare co‐users of alcohol and marijuana to alcohol‐only users on willingness to experience consequences, and examine the role of willingness as a mediator between co‐user status and consequences experienced. Co‐users were more willing to experience adverse effects from drinking, in turn predicting more consequences. Intervention work targeting consequences may be less effective for co‐users; thus, additional work is needed to identify other potential mechanisms for change for this at‐risk group. Abstract : The current study explored willingness to experience negative consequences as a potential factor underlying the association between alcohol and marijuana co‐user status and negative consequences. Relative to alcohol‐only users, co‐users were more willing to experience adverse effects from drinking, in turn predicting more consequences. Intervention work targeting consequences may be less effective for co‐users, thus additional work is needed to identify other potential mechanisms for change for this at‐risk group.